(untitled) (Construction Economics and Building, 2022)
The potential to promote health and safety (H&S) through public procurement has resulted in increased expectation for public sector clients to integrate H&S matters into their procurement decisions and practices. Developing countries are however far behind in this endeavour. Using qualitative research, therefore, this study explored how public clients integrate H&S into the procurement of public works. Data was collected through semi-structured interviews with 20 contractors and public sector clients who have vast experience in the procurement of public works. The data was analysed using both inductive and deductive thematic analyses. The findings show that the extent of H&S integration into the procurement process depended on the funding source(s) for public projects. H&S matters are generally overlooked in the various procurement stages for public projects funded by the government, while in those funded by international development agencies, H&S matters are prioritized, and therefore, given considerable attention. The research contributes to construction H&S improvement research in developing countries by giving insight into the extent of H&S integration into public procurement. It also contributes to the understanding of the influence of funding sources on the extent to which H&S matters are integrated into public procurement in developing countries.